2015
DOI: 10.3945/ajcn.114.100305
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cholesterol and cardiovascular disease: a systematic review and meta-analysis

Abstract: Reviewed studies were heterogeneous and lacked the methodologic rigor to draw any conclusions regarding the effects of dietary cholesterol on CVD risk. Carefully adjusted and well-conducted cohort studies would be useful to identify the relative effects of dietary cholesterol on CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
0
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(204 citation statements)
references
References 70 publications
6
173
0
9
Order By: Relevance
“…Although rich in healthy food components such as phospholipids, the carotenoids lutein and zeaxanthin, and many vitamins, the high content of dietary cholesterol in eggs has garnered the most attention with respect to health. Meta-analyses of intervention trials have shown that an increased intake of dietary cholesterol increases serum total, LDL, and HDL cholesterol concentrations, as well as the ratio of total and LDL cholesterol to HDL cholesterol (1,2). However, findings from trials of the effects of high egg consumption on lipid profile concentrations have not been consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Although rich in healthy food components such as phospholipids, the carotenoids lutein and zeaxanthin, and many vitamins, the high content of dietary cholesterol in eggs has garnered the most attention with respect to health. Meta-analyses of intervention trials have shown that an increased intake of dietary cholesterol increases serum total, LDL, and HDL cholesterol concentrations, as well as the ratio of total and LDL cholesterol to HDL cholesterol (1,2). However, findings from trials of the effects of high egg consumption on lipid profile concentrations have not been consistent.…”
Section: Introductionmentioning
confidence: 99%
“…In such studies, however, greater doses of cholesterol than the average Japanese intake have typically been employed as intervention. The mean cholesterol intakes of Japanese adults are 338 mg/d for men and 279 mg/d for women (1), while the doses used in many trials ranged from 500 to 1,400 mg/d (2). Thus, further trials with moderate cholesterol intakes are indispensable to better understand the possible effects of typical cholesterol intakes in healthy populations.…”
mentioning
confidence: 99%
“…Diabetes mellitus is one of the risk factors that can cause atherosclerosis. 8 LDL cholesterol levels play a major role in the incidence of cardiovascular disease. Based on the results of this study, 96% subjects had LDL level > 100 mg.dl.…”
Section: Results Dan Discussionmentioning
confidence: 99%